Evaluation of Salvadora persica L. and green tea anti-plaque effect: a randomized controlled crossover clinical trial - Abdulbaqi, H.R.; Himratul-Aznita, W.H.; Baharuddin, N.A. (BioMed Central, 2016)
Background: In the author's earlier in vitro investigation, a combination of 0.25 mg/ml green tea and 7.82 mg/ml Salvadora persica L. aqueous extracts was found to exhibit significant synergistic anti-bacterial and anti-adherence effects against primary plaque colonizers biofilm. A clinical trial was needed to support these preliminary in vitro results and to investigate its efficacy as a mouthwash in the control of dental plaque. Methods: A 24 h plaque re-growth, double-blinded, randomized crossover trial was carried out. Participants (n = 14) randomly rinsed with test formulation, 0.12% chlorhexidine (control) and placebo mouthwashes for 24 h. A week before the trial, all participants received scaling, polishing and oral hygiene education. On the trial day, the participants received polishing at baseline and rinsed with 15 ml of randomly allocated mouthwash twice daily without oral hygiene measures. After 24 h, plaque index was scored and then the participants entered a 6-days washout period with regular oral hygiene measures. The same protocol was repeated for the next 2 mouthwashes. Results: The results were expressed as mean (±SD) plaque index. The test mouthwash (0.931 ± 0.372) significantly reduced plaque accumulation when compared with placebo (1.440 ± 0.498, p < 0.0167) and chlorhexidine (1.317 ± 0.344, p < 0.0167) mouthwashes. No significant difference was found between chlorhexidine and placebo (p > 0.0167). Conclusions: The test mouthwash has an anti-plaque effect for a 24 h period. Longer-term clinical studies are highly encouraged to investigate its anti-plaque effect for longer periods. Trial registration: This study was registered in ClinicalTrials.gov as NCT02624336in December 3, 2015.